Exploratory multivariate analysis by example using R - Husson, François, 1970-; Lê, Sébastien, 1973-; Pagès, Jérôme, 1949- (Chapman & Hall/CRC computer science & data analysis series, 2010)
"An introduction to exploratory techniques for multivariate data analysis, this book covers the key methodology, including principal components analysis, correspondence analysis, mixed models and multiple factor analysis. The authors take a practical approach, with examples leading the discussion of the methods and lots of graphics to emphasize visualization. They present the concepts in the most intuitive way possible, keeping mathematical content to a minimum or relegating it to the appendices. The book includes examples that use real data from a range of scientific disciplines and implemented using an R package developed by the authors"-- Anotace od vydavatele